Capacitated Transport Vehicle Routing for Joint Distribution in Supply Chain Networks - Mojahid F Saeed Osman (International Journal of Supply Chain Management, 2016)
This paper addresses the problem of capacitated transport vehicle routing for joint distribution of different suppliers. Although all suppliers distribute similar products to cities within the same region, each supplier has an extensive distribution network. In this paper, we develop solution procedures that guide the problem-solving process and quickly lead to a good routing solution. A case study is introduced with three real-world case problems for illustrating the applicability and suitability of the proposed approach. The results show that solution procedure approach for is more than reasonable for quickly constructing good transport vehicle routes.